Multiple Inflammatory Biomarkers in Relation to Cardiovascular Events and Mortality in the Community - Schnabel, Renate B. (2013)
OBJECTIVE: Evidence suggests that chronic low-grade inflammation and oxidative stress are related to cardiovascular disease (CVD) and mortality. APPROACH AND RESULTS: We examined 11 established and novel biomarkers representing inflammation and oxidative stress (C-reactive protein [CRP], fibrinogen, interleukin-6, intercellular adhesion molecule-1 [ICAM-1], lipoprotein-associated phospholipase A2 (mass and activity), monocyte chemoattractant protein-1, myeloperoxidase, CD40 ligand, P-selectin, tumor necrosis factor receptor II [TNFRII]) in relation to incident major CVD and mortality in the community. We studied 3035 participants (mean age 61±9 years, 53% women). During follow-up (median 8.9 years), 253 participants experienced a CVD event and 343 died. CRP (hazard ratios [HR] reported per standard deviation ln-transformed biomarker, 1.18, 95% confidence interval [CI] 1.02-1.35; nominal P=0.02) and TNFRII (HR 1.15, 95% CI; 1.01-1.32; nominal P=0.04) were retained in multivariable-adjusted models for major CVD, but were not significant after adjustment for multiple testing. The biomarkers related to mortality were TNFRII (HR 1.33, 95% CI: 1.19-1.49; P<0.0001); ICAM-1 (HR 1.24, 95% CI: 1.12-1.37; P<0.0001), and interleukin-6 (HR 1.25, 95% CI: 1.12-1.39; P<0.0001). The addition of these markers to the model including traditional risk factors increased discrimination and reclassification for risk of death (P<0.0001), but not for CVD. CONCLUSIONS: Of 11 biomarkers, TNFRII was associated nominally with incident major CVD, and significantly with all-cause mortality, which renders it an interesting target for future research. The combination of TNFRII with CRP in relation to CVD and with interleukin-6 to mortality increased the predictive ability in addition to CVD risk factors for total mortality but not for incident CVD.